The raging storm - Hunter, Erin (New York, NY : Harper, 2019)
Tigerstar now leads ShadowClan, and for the first time there are five strong clans around the lake. But there is still no peace as ShadowClan and SkyClan experience familiar tension along their borders, and Tigerstar threatens to undo all the work Alderheart, Violetshine, and Twigbranch have done to achieve peace. Meanwhile, the storm StarClan has been warning about is coming, and their warnings more intense as disease, conflict, and doubt infect every camp, leaving all five clans in peril.
4.3.
5-8.
600
Accelerated Reader AR
Keywords: Cats -- Fiction; Adventure fiction; Fantasy fiction; Animals -- Fiction